Microbiological findings after periodontal therapy using curettes, Er:YAG laser, sonic, and ultrasonic scalers - Foteini V. Derdilopoulou (Blackwell Synergy, 2007)
Aim: To evaluate and compare the microbiological effects of hand instruments, Er:YAG-laser, sonic, and ultrasonic scalers in patients with chronic periodontitis. Patient perception of each treatment was documented. Material and Methods: From 72 patients, bacterial samples were collected from the deepest pocket in each quadrant (total: 288 sites). A polymerase chain reaction kit estimated the amount of Aggregatibacter (Actinobacillus) actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), Tannerella forsythensis (Tf), and Treponema denticola (Td) at baseline as well as 3 and 6 months after therapy. One quadrant in each patient was randomly assigned to curettes (H-group), Er:YAG laser (L-group), sonic device (S-group), or ultrasonic device (U-group). Results: Three months post-operatively, the amounts of Pg, Pi, Tf, and Td were significantly reduced in all groups. Laser and sonic instrumentation failed to reduce Aa. Six months after therapy, significant differences were still detected for Pg (L- and U-group), for Pi and Tf (S-group), and for Td (L-, S- and U-group). Patients rated ultrasonic treatment as more preferable than hand and laser instrumentation. Conclusion: The various treatment methods resulted in a comparable reduction of the evaluated periodontal pathogens, and bacterial increase was only partially different 6 months post-operatively. Ultrasonic instrumentation caused less discomfort.